AȘTEPTÂND PRUTUL „SĂ SACE”... - MISCHEVCA, Conf. dr. , Vlad (BIBLIOPOLIS, 2020)
The Prut is an interne river, became „international”, which divides three stats: Romania, Republic of Moldova and Ucraine. After the Second World War the consequences of the Ribbentrop-Molotov pact continue to be perpetuated, and the determintion of the last frontier on the Prut River is equivalent to raising a new Berlin Wall in Europe. The river itself can’t be good or bad, in geographical terms. The splitting of nation and setting of arbitrary borders attracted the attention of many writers, historians and cultural personnalities. The article prezented a summary approach of the dramatic Prut history and is away from the thought of an exhaustive prezentation.